Short-chain ketone production by engineered polyketide synthases in Streptomyces albus. Issue 1 (December 2018) - Yuzawa, Satoshi; Mirsiaghi, Mona; Jocic, Renee; Fujii, Tatsuya; Masson, Fabrice; Benites, Veronica; Baidoo, Edward; Sundstrom, Eric; Tanjore, Deepti; Pray, Todd; George, Anthe; Davis, Ryan; et al.
Abstract Microbial production of fuels and commodity chemicals has been performed primarily using natural or slightly modified enzymes, which inherently limits the types of molecules that can be produced. Type I modular polyketide synthases (PKSs) are multi-domain enzymes that can produce unique and diverse molecular structures by combining particular types of catalytic domains in a specific order. This catalytic mechanism offers a wealth of engineering opportunities. Here we report engineered microbes that produce various short-chain (C5–C7) ketones using hybrid PKSs. Introduction of the genes into the chromosome ofStreptomyces albus enables it to produce >1 g · l−1 of C6 and C7 ethyl ketones and several hundred mg · l−1 of C5 and C6 methyl ketones from plant biomass hydrolysates. Engine tests indicate these short-chain ketones can be added to gasoline as oxygenates to increase the octane of gasoline. Together, it demonstrates the efficient and renewable microbial production of biogasolines by hybrid enzymes. Mutating natural enzymes is effective in broadening the substrate or product range, but generally leads to reduced titers. Here the authors engineer hybrid polyketide synthases for efficient production of short-chain ketones from plant biomass hydrolysates inStreptomyces, which can increase the octane of gasoline.